Gee die Bybel nog vandag aan ons morele oriëntering oor kwessies soos homoseksualiteit? - E. de Villiers (Acta Theologica)
In the introduction to this article an attempt is made to indicate why this issue has become relevant, if not urgent, in the so-called Afrikaans churches. The next section highlights the emphasis by contemporary biblical scholars on the influence of the context within which the various books of the Bible were written. Some less convincing proposals regarding the way in which the moral guidance of Scripture can today be affirmed are then discussed. A more satisfactory affirmation is proposed, with the basic moral orientation in the Bible as point of departure. This proposal is then applied in an attempt to answer the question “What moral guidance does the Bible provide regarding the contemporary issue of homosexuality?”